International Aid in Managing IDPs: The Case of United Nations in Nigeria - Oluwafunke Adeola Adeleye; Oluwaseun Samuel Osadola (Budapest International Research and Critics University, 2022)
Human displacement has been a recurring factor in international affairs. This, on one hand is a result of trans-border displacement while on the other hand, is due to the intensity of internal displacement and its attendant need for protection and assistance of internally displaced persons. International aid has remained a constant theme in human displacement in general even when internally displaced persons are basically the responsibility of their government. This research examines the interventions of United Nations in the management of internally displaced persons in Nigeria. It made use of both primary and secondary sources of data. The major instrument of research was oral interview of key respondents. The research found out that the United Nations, through its specialised agencies has been playing significant roles in all facets of protection, relief and development of internally displaced persons in Nigeria. The United Nations interventions were observed in the provision of basic healthcare, education, shelter, security,food and non-food items, orientation, durable solution and psychosocial support. The research concludes that, international aid, especially from the United nations has been strategic to the management of the humanitarian crisis in Nigeria. But despite the volume of the interventions, the high population of the IDPs continue to overshadow it.